(untitled) (Patan Pragya, 2019)
This paper investigated the relationship between liquidity and profitability of Nepalese commercial banks. The main objective was to explore and examine the liquidity position, profitability status and relationship between liquidity and profitability in of Nepalese commercial banks. This study based on secondary data from the annual reports of the Nepalese commercial banks and NRB over a period of past 10 fiscal years from 2007/08 to 2019/17in Nepal. Correlation and regression analysis were employed to examine the relationship between liquidity and profitability. The ROA, ROE and net profit margin was used to measure profitability status and current ratio, cash and bank balance to total deposit and cash and bank balance to current deposit ratio was used to measure liquidity position. The findings of this paper are based on a study conducted on the selected banks. Hence, the results show that ADBL and NABIL have good liquidity position and profitability position. Therefore, the results are valid for banking sector.